The Inter-American System of Protection of Human Rights - Rodríguez-Rescia, Víctor (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The American Declaration of the Rights and Duties of Man of 1948, which provides the framework for the whole system, plays an important role for those Member States that have not ratified the American Convention, but also to the States that are parties of it, because it operates as customary law and is a source of a fundamental right, as even supplies legal loopholes as in the case of economic, social and cultural rights. Indeed, 1998 marked the fiftieth anniversary of this important regional instrument that, also for the proud of Americans, preceded by a few months to the Universal Declaration of Human Rights.